Produksi dan Konsumsi Oksigen serta Pertumbuhan Ceratophyllum demersum L. pada Kerapatan yang Berbeda dalam Mendukung Potensinya sebagai Bioaerator - Hidayat, Muhammad Khusni; Izzati, Munifatul; Setiari, Nintya (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2011)
Aquaculture is one of important economic activity in Indonesia. The main problem in aquaculture is the low water quality such lower oxygen level . Ceratophyllum demersum is one of aquatic plants that is hypothesized capable in increasing oxygen level through photosynthesis. However the growth of C. demersum it self will consume oxygen from the waterÂ through respiration. The aim of this study is to measure oxygen production and consumption by C. demersum at different density level. From this data, we will understand the potency ofÂ C.demersum as bioaerator to supplay oxygen in the water. This experiment was designed using Completed Randomized Designed (CRD). Three density level of C. demersum was apllied as treatment. They were 100g/100L, 200g/100L dan 300g/100L. Each treatment was replicated by 4 times. Results indicated that in density of 300g/100L produced the highest oxygen level ( 1,65 ppm). The highest growth rate of C. demersum was resulted by density level of 200g/100L.